Revisiting the Role of Mindfulness-based Stress Reduction in the Management of Rheumatoid Arthritis - Praveen Deepak (International Journal of Vaccines, 2024)
Rheumatoid arthritis (RA) is a type of arthritis characterized by a chronic inflammatory disorder that primarily affects the lining of the synovial joints resulting in progressive disability in the movement of diarthrodial joints and arthralgia. It is a debilitating disease associated with premature death and socioeconomic burdens. Its pathogenesis is multifactorial with an individual course of progression where psychological stress is considered to be one of the risk factors associated with RA progression. Most of the therapeutic interventions rely upon the use of NSAIDs, DMARDs, tumor necrosis factor Inhibitors, and more recent T-cell costimulatory blocking agents, B-cell depleting agents, and Interleukin-1 antagonists but, all these modalities lead to severe side effects and havoc on the quality of life of RA patients. Recently, psychological stress is a prominent risk factor that is associated with the pathogenesis of RA and induces flare response in RA patients which indicates the implication of intervention of psychological treatment to RA patients. Recently, Mindfulness-Based Stress Reduction (MBSR) perceived to be an effective modality for the management of RA that has the potential to improve the quality of life of RA patients under medication. However, the extent of this contribution to MBSR is not clear, therefore this review aims to understand the effects of MBSR in patients with RA by searching related literature on databases like Google Scholar, PubMed, Embase, and Web of Science. This study encompasses different interventions of MBSR, such as mindfulness meditation, mindfulness yoga, mindfulness exercise, etc, as a therapeutic modality for RA.
Keywords: Meditation; Mindfulness-Based Stress Reduction (MBSR); Pathogenesis; Psychological Stress; Rheumatoid Arthritis (RA); Yoga